2012
DOI: 10.1590/s1517-83822012000100026
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol in combination with N-acetylcysteine against Staphylococcus epidermidis planktonic and biofilm cells

Abstract: Staphylococcus epidermidis is the most frequent cause of nosocomial sepsis and catheter-related infections, in which biofilm formation is considered to be the main virulence mechanism. In biofilm environment, microbes exhibit enhanced resistance to antimicrobial agents. This fact boosted the search of possible alternatives to antibiotics. Farnesol and N-acetylcysteine (NAC) are non-antibiotic drugs that have demonstrated antibacterial properties. In this study, the effect of farnesol and NAC isolated or in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…We have recently shown that farnesol increased cell death by the action of tetracycline or rifampicin [20], possibly due to the permeabilization of the cell wall [22]. The same was true in combination with N -acetylcysteine [27]. However, the exact mechanism of farnesol action in S. epidermidis is not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that farnesol increased cell death by the action of tetracycline or rifampicin [20], possibly due to the permeabilization of the cell wall [22]. The same was true in combination with N -acetylcysteine [27]. However, the exact mechanism of farnesol action in S. epidermidis is not fully known.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its antibacterial activity against planktonic bacteria, NAC is a mucolytic agent that acts against biofilms by reducing the production of extracellular polysaccharide and adhesion of bacteria on surfaces . The antibiofilm activity of NAC against several microbial biofilms has been demonstrated in the medical literature . Recently, Quah et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antibacterial activity against planktonic bacteria, NAC is a mucolytic agent that acts against biofilms by reducing the production of extracellular polysaccharide and adhesion of bacteria on surfaces (27,28). The antibiofilm activity of NAC against several microbial biofilms has been demonstrated in the medical literature (27)(28)(29)(30). Recently, Quah et al (7) reported that NAC was effective against both the planktonic and biofilm forms of E. faecalis at pH 11 and that the presence of dentin powder did not reduce its antibacterial activity for up to 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence also suggests that antibiotics may be a necessary addition to ensure elimination of contamination [3,4,6]. While reduction in biofilm biomass was observed using DAAs alone, complete eradication was not observed even at the highest concentrations studied.…”
Section: How Do We Get There?mentioning
confidence: 98%
“…D-amino acids (D-AAs), cis 2-decenoic acid, and farnesol are among these recently discovered biofilm inhibitors that have been shown to prevent biofilm formation, disperse existing biofilm, and revert persister cells to a more active and antimicrobial-susceptible state [4,7,8] Recent studies of antiinfective strategies for implanted materials have highlighted the need for inclusion of biofilm-targeting therapy in addition to antibiotics [1,5]. In the study by Harmata and colleagues, the specific inhibition and dispersal of both methicillin-susceptible and methicillin resistant Staphylococcus aureus strains were confirmed at particular D-AA concentrations.…”
mentioning
confidence: 99%